2017
DOI: 10.1016/j.clay.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow and effective conductivity calculations on numerical images of bentonite microstructure

Abstract: Hydraulic conductivities of compacted water-saturated bentonite were computed based on the real microstructure. The Homogenization of Periodic Media approach employed fully acknowledges the heterogeneous and multiscale microstructure of clay, as well as locally varying physical flow properties. Consequently, three levels of description were considered : the microscopic level of clay particles, the mesoscopic level of clay aggregates, mineral grains and inter-aggregate porosity, and the macroscopic level of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies have indicated that pore tortuosity serves as a non-negligible factor in determining the hydraulic conductivity of soil [ 6 , 35 , 45 , 75 , 76 , 77 , 78 , 79 , 80 ]. Pore tortuosity is defined as the ratio of the effective path length ( L e ) to the sample length ( L ) [ 45 , 81 , 82 ], …”
Section: Theory and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that pore tortuosity serves as a non-negligible factor in determining the hydraulic conductivity of soil [ 6 , 35 , 45 , 75 , 76 , 77 , 78 , 79 , 80 ]. Pore tortuosity is defined as the ratio of the effective path length ( L e ) to the sample length ( L ) [ 45 , 81 , 82 ], …”
Section: Theory and Methodologymentioning
confidence: 99%
“…Bentonite is a widely considered swelling clay as an engineered barrier material in geological waste disposal because it has a large percentage of smectite (50~90%), a clayey soil swelling under water intrusion. Bentonite has lower hydraulic conductivity and diffusivity, and higher expansive capacity, specific surface area, cation-exchange potential, and thermal conductivity compared to other soils [ 1 , 2 , 3 , 4 , 5 , 6 ]; therefore, it plays a key role in various geo-environmental engineering applications, such as containment systems, carbon dioxide storage [ 7 , 8 ], bioremediation [ 9 ], and stability of petroleum reservoirs [ 10 ]. Bentonite has been attracting attention in the construction of disposal repository of high-level nuclear waste for 4 decades [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The thresholding procedure is based on the algorithm of maximization of the gray level histogram's entropy developed by (Kapur et al, 1985). The threshold values obtained are validated by comparison of the resulting phase proportions with the cumulative distribution curve and the initial known phase proportions (Bouchelaghem and Pusch, 2017;Tomioka et al, 2010). The contours are extracted separately for each phase using Moore-Neighboor's algorithm with Jacob's stopping criterion, before being imported and used to create the Finite Element mesh in Castem.…”
Section: At the Mesoscopic Scalementioning
confidence: 99%